REGISTER NELAYAN ALE—ALE DI DESA SUKA BANGUN KECAMATAN DELTA PAWAN KABUPATEN KETAPANG - Endah Nur Saqinah; Laurensius Salem; Agus Syahrani (Universitas Tanjungpura, 2022)
This study aims to analyze language variations, namely the register used by ale-ale fishermen in Ketapang Regency. The research method used is descriptive and the form of this research is qualitative research. The data in this study are in the form of utterances used by fishermen during catching ale-ale. The data collection technique used is the listening technique with the tapping method. The results of the analysis show that there are 32 registers used by ale-ale fishermen. Based on the results of the analysis, there are 12 closed registers and 20 open registers. In addition, there are 5 registers that have changed meaning. Based on the results of the analysis that has been carried out, it is hoped that it can add insight and new vocabulary in the Ketapang Malay dialect dictionary.